Preparation of isolated Co3O4 and fcc-Co crystallites in the nanometre range employing exfoliated graphite as novel support material. Issue 8 (13th June 2019) - Wolf, Moritz; Fischer, Nico; Claeys, Michael
Abstract : The inert nature of graphitic carrier materials allows for characterisation of rather isolated supported nanoparticles in model catalysts – as long as sufficiently large inter-particle distances are obtained. Abstract : The inert nature of graphitic samples allows for characterisation of rather isolated supported nanoparticles in model catalysts, as long as sufficiently large inter-particle distances are obtained. However, the low surface area of graphite and the little interaction with nanoparticles result in a challenging application of conventional preparation routes in practice. In the present study, a set of graphitic carbon materials was characterised in order to identify potential support materials for the preparation of model catalyst systems. Various sizes of well-defined Co3 O4 nanoparticles were synthesised separately and supported onto exfoliated graphite powder, that is graphite after solvent-assisted exfoliation via ultrasonication resulting in thinner flakes with increased specific surface area. The stability of the supported nanoparticles during reduction to metallic cobalt in H2 was monitored in situ by means of X-ray diffraction and smaller crystallite sizes were found to be harder to reduce than their larger counterparts. A low cobalt loading of 1 wt% was required to avoid aggregates in the parent catalyst, and this allowed for the preparation of supported cobalt nanoparticles which were resistant to sintering at reduction temperatures below 370 °C. The developed model catalysts are ideally suited for sintering studies of isolated nano-sized cobalt particles as the graphitic support material does not provide distinct metal–support interaction. Furthermore, the differently sized cobaltous particles in the various model systems render possible studies on structural dependencies of activity, selectivity, and deactivation in cobalt oxide or cobalt catalysed reactions.